(untitled) (Journal of Chitwan Medical College, 2023)
Background: Underweight children are those whose weight-for-age Z-score is less than minus two standard deviations (-2 SD) from the reference population median. Children who are malnourished during their first two years of life and gain weight quickly later in childhood and adolescence are at a significant risk of developing chronic disorders connected to nutrition. This study aimed to explore the factors associated with underweight among the children below 24 months. Methods: A cross-sectional study was conducted among 304 mothers with children below 24 months. Probability proportional to size (PPS) method was used to identify the sample size in each ward and simple random sampling with lottery method was used to select the children from each ward. Data was collected through face-to-face interview using a pre-tested structured questionnaire and anthropometric measurement. Data were processed using IBS SPSS v.16.0. Results: The prevalence of underweight among children below 24 month was found to be 25% (76). In this study ethnicity of a children (p≤ 0.001), occupation of a mother (p=0.018), mother’s age at her first baby (p=0.014), and age of a children (p=010) and diarrhea in last 6 months (p=0.000) were found to be associated with underweight. Conclusions: The study identified that ethnicity, age of mother at her first baby, occupation of mother, age of children and sign of diarrhea in children were associated with underweight. Different family and child health related programs should be done to provide education about the childhood illness and infestation, child feeding practices and healthy care of child in order to reduce the underweight.